Memaknai Pengakuan Iman Yesus adalah Kristus bagi Mahasiswa STAK Reformed Remnant Internasional - Debbie Yohanna Refialy (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2022)
Confession of faith should not only be a confession on the mouth only, but must come to real application in daily life. The purpose of this research was to determine the extend to which the understanding of the confession that Jesus is the Christ and the application in the daily life of STAK-RRI students. This research uses qualitative biblical theology research methods and uses data collection techniques through observation and interviews. From the research, it is concluded that: First, just having knowledge that Jesus is the Christ will not have much impact in daily life.  Second, Confession that Jesus is the Christ only occurs through knowing Jesus according to God's time schedule for each person.  This research is expected to contribute to the real application of the confession of faith in daily life.